Validity of the three apathy items of the Geriatric Depression Scale (GDS‐3A) in measuring apathy in older persons. (7th April 2016) - Bertens, Anne Suzanne; Moonen, Justine E.F.; de Waal, Margot W.M.; Foster‐Dingley, Jessica C.; de Ruijter, Wouter; Gussekloo, Jacobijn; van der Mast, Roos C.; de Craen, Anton J.M.
Abstract : Objective: The Geriatric Depression Scale (GDS)‐3A, a three‐item subset of the GDS‐15, is increasingly used as a measure for apathy in research settings to assess factors associating with this neuropsychiatric syndrome. We aimed to assess how accurately the GDS‐3A discriminates between presence and absence of apathy in two populations of community‐dwelling older persons, using the Apathy Scale as reference standard. Methods: Baseline data were used from 427 participants of the Discontinuation of Antihypertensive Treatment in Elderly people (DANTE) Study Leiden and 1118 participants of the PROactive Management Of Depression in the Elderly (PROMODE) Study, all ≥75 years and with available GDS‐3A and Apathy Scale measurements. A cut‐off score of ≥14 was used for presence of apathy according to the Apathy Scale. Areas under the receiver operating characteristic curve (AUC) were calculated. Based on the likelihood ratios for GDS‐3A scores, a cut‐off of ≥2 was used for presence of apathy according to the GDS‐3A to calculate test characteristics. Results: The AUC was 0.68 (95% confidence interval 0.62–0.73) in the DANTE Study and 0.72 (0.67–0.77) in the PROMODE Study. In the DANTE Study sensitivity was 29.3% (21.4–38.1) and specificity was 88.5% (84.4–91.8), whereas in the PROMODE Study sensitivity was 32.8% (24.5–41.1) and specificity 92.6% (90.9–94.2). Stratification on population characteristics did not yield more favourable test characteristics. Conclusion: The GDS‐3A has low sensitivity and high specificity as a measure of apathy in two populations of older persons. Using the GDS‐3A in research might yield estimates biassed towards the null in case of non‐differential misclassification. Copyright © 2016 John Wiley & Sons, Ltd.